Condutividade elétrica e composição mineral da solução de embebição de sementes de feijão armazenadas em duas temperaturas - Silva, Claudia Denise [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Modern agriculture requires quick tests to evaluate the seeds quality, in order to determine their potential use. The electrical conductivity test has been used for many species, especially legumes seeds. This research was carried out in order to investigate the relationship between the amount of electrolytes (K+, Ca++ and Mg++) on the seed soaked solution and the vigor measured by electrical conductivity test of bean seeds (Phaseolus vulgaris L.) stored at 10 and 25 °C. Three seed lots cultiv ar IAPAR - 81 (Carioca Group) and three cultivar IPR - TIZIU (black group) were stored in a cold chamber at 10 °C and in a BOD at 25 °C. Eval uations were done in intervals of three months over a 12 months and the variables were: water content, germination and vigor (accelerated aging and electrical conductivity tests). The potassium content in the imbibition solution was determined by flame photometry and the calcium and magnesium contents, by atomic absorption spectrophotometry. The statistics model used was completely randomized design in a factorial (four periods of storage X three temperatures) with additional treatment (initial assessment) with four replicates for each lot. The cultivars showed similar behavior in storage. Electrical conductivity values decreased in the last evaluation and it was not followed by reduction of the ions quantified. The potassium was the ion leached in larger amounts from bean seeds stored, and it´s behavior was closest to the results of electrical conductivity test.

A agricultura moderna exige testes rápidos para avaliação da qualidade de sementes para determinar o seu uso potencial. O teste de condutividade elétrica é usado para sementes de muitas espécies, especialmente as de leguminosas. O objetivo dessa pesquisa foi o de avaliar o efeito da temperatura de armazenamento sobre os resultados do teste de condutividade elétrica e da composição mineral da solução de embebição de sementes de feijão (Phaseolus vulgaris L.) armazenadas durante um ano a temperatura de 10 e 25 °C. Foram utilizados três lotes da cultivar IAPAR – 81 (grupo carioca) e três lotes da cultivar IPR – TIZIU (grupo preto) armazenadas em câmara fria a 10 °C e em BOD a 25 °C. As avaliações foram reali zadas em intervalos de três meses ao longo de 12 meses e as variáveis avaliadas foram: teor de água, germinação e vigor (envelhecimento acelerado e condutividade elétrica). O conteúdo de potássio da solução de embebição foi determinado por fotometria de chama e o conteúdo de cálcio e magnésio por espectrofotometria de absorção atômica. Os dados foram analisados segundo o delineamento inteiramente casualizado em esquema fatorial (4 períodos de armazenamento x 3 temperaturas) com tratamento adicional (avaliação inicial) com quatro repetições para cada lote. As sementes das cultivares apresentaram comportamento semelhante no armazenamento.
Keywords: Phaseolus vulgaris L.; Vigour; Leach; Magnesium; potassium; Calcium; Sementes - Armazenamento; Lixiaviação; Cálcio; Potassio; Magnésio; Vigor